Artificial intelligence and cybersecurity - Zadorozhna Olexandra; Hanna Sorokun (Закарпатський угорський інститут імені Ференца Ракоці II, 2024)
Abstract. In today’s world the Internet has become the invaluable tool of communication, education and entertainment, but it also has given rise to a huge amount of various forms of exploitation and abuse, targeting minors. Artificial Intelligence (AI) plays a pivotal role in detecting and preventing child abuse as well as it may be misused by cybercriminals to create different forms of exploitation, such as deepfakes or AI-generated Child Sexual Abuse Material (CSAM). Given the widespread and consistently evolving nature of these threats, the issue of developing the robust AI-driven solutions to combat them has never been more pressing.
Keywords: Artificial Intelligence; cybercriminal